Edukasi Literasi Keuangan Pada Pengurus Ranting 'Aisyiyah Ngasem Kecamatan Colomadu - Erikawati, Civi; Aini Intan Muktiana, Nurul; Via Febrianti, Nur (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The aim of this Community Service is to provide education and understanding to the administrator of Aisyiyah Ranting Ngasem, Colomadu about the importance of financial literacy. The method we use is to provide education to the public in the hope of providing awareness, understanding and being able to apply financial literacy in everyday life. In carrying out this community service, the event ran smoothly, participants listened enthusiastically, actively asked questions and discussed. Of the total 50 participants, 50% understood the material that had been presented. The hope from the results of this activity is that participants will be able to understand financial literacy and apply it by implementing the importance of investment as a solution when inflation occurs. The next program for community service is education regarding financial literacy by implementing the National Cashless Movement (GNNT) as planned by the government.